The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13277-015-3073-3
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide induces apoptosis of F9 mouse teratocarcinoma stem cells by downregulation of SATB1 expression

Abstract: The aim of this study was to decide whether nicotinamide (NA) could induce apoptosis of F9 mouse teratocarcinoma stem cells (MF9) by downregulation of special AT-rich sequence binding protein 1 (SATB1) expression. We used different concentrations of NA (0, 1.5, 2, and 2.5 mmol/L) to treat MF9 cells and analyze SATB1 expression by RT-qPCR and Western blotting; in addition, the cell proliferation was detected in a microplate reader with Cell Counting Kit-8 (CCK-8), and the cell cycle and apoptosis were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Data reported in the present study support a mechanism likely related to an early alteration of cellular energy metabolism. In fact, we observed that NAM treatment increases NAD + , ATP, and ROS levels at as early as 6 h treatment and leads to a significant increase of cells in G1 phase and relevant depletion of cells in S-G2 phase and a strong increase of cells in apoptosis (sub-G1 phase) at 24 h. Of note, NAM has been shown to induce apoptosis also in mouse teratocarcinoma stem cells [ 54 ] and increased intracellular levels of ATP have been related to cytotoxic effects in other cell types [ 55 ]. All such early effects paralleled the relevant cell number reduction and cell death induction observed at 24 and 48 h treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data reported in the present study support a mechanism likely related to an early alteration of cellular energy metabolism. In fact, we observed that NAM treatment increases NAD + , ATP, and ROS levels at as early as 6 h treatment and leads to a significant increase of cells in G1 phase and relevant depletion of cells in S-G2 phase and a strong increase of cells in apoptosis (sub-G1 phase) at 24 h. Of note, NAM has been shown to induce apoptosis also in mouse teratocarcinoma stem cells [ 54 ] and increased intracellular levels of ATP have been related to cytotoxic effects in other cell types [ 55 ]. All such early effects paralleled the relevant cell number reduction and cell death induction observed at 24 and 48 h treatment.…”
Section: Discussionmentioning
confidence: 99%